Pengaruh Akad Murabahah terhadap Pengembangan Ekonomi Santri di Pesantren KHAS Kempek Cirebon - Syukron, Ahmad; Fawwaz, Ahmad; Aripin, Pipin_Zaenal (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2026)
This study aims to describe the implementation of the murabahah contract at KHAS Kempek Islamic Boarding School and analyze its impact on the economic development of the students. The research method uses a descriptive qualitative approach, with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the implementation of murabahah at this boarding school is in accordance with the principles of Islamic economic law, including price transparency, initial agreements, and the avoidance of usury (riba) and excessive uncertainty (gharar). The interest-free payment mechanism and strict Sharia supervision strengthen the integrity of the transactions. Murabahah has a significant positive impact on the economic empowerment of santri, ranging from easier access to capital, enhanced entrepreneurial capacity, to contributions to local economic development. However, challenges such as understanding the technical aspects of the contract and the limitations of cooperative capital still need to be addressed through strengthening Islamic economic literacy and external collaboration. These findings contribute to the development of knowledge and practice in pesantren-based Islamic economics and support the sustainable economic independence of santri.